PENGUATAN MANAJEMEN KELOMPOK PETANI PEMAKAI AIR DAN KELOMPOK PENDUDUK PEMAKAI AIR MINUM - Gatot Sugeng Purwono (RELASI : JURNAL EKONOMI, 2013)
Farmer Water User Association (HIPPA) is a non-governmental organization whose establishment stipulated in Government Regulation No. 20 of 2006 on Irrigation . HIPPA role as management of irrigation at the farm/village, aims to support the aspirations of farmers and land productivity in order to increase agricultural production, food security, and livelihoods. HIPPA formation in the institution is expected to be independent and have the ability in the field of organizational, economic and technical. The problem, HIPPA role yet as expected. HIPPA involvement in the determination of government policy and the development forum (especially irrigation) from the village, sub-district,  and district almost nothing . Often occurs when the tissue rehabilitation, contractors not communicating with HIPPA as irrigation management institutions and farmer representatives . As a result, many activities that deviate from the target , resulting in a decline in the quality of the work. HIPPA therefore need to be empowered role for supervision of construction services activities which will greatly assist the development and management of irrigation systems.